Hubungan Kualitas Layanan Administrasi Kesiswaan dengan Kepuasan Peserta Didik SMK Negeri 2 Siatas Barita - Hotmarito Romauli Hutabarat (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The purpose of this study was to determine the relationship between the quality of student administration services and student satisfaction at SMK Negeri 2 Siatas Barita in the 2024/2025 Academic Year. The method used in this study is the inferential quantitative method. The population was all students of SMK Negeri 2 Siatas Barita totaling 741 people and a sample of 74 people was determined using a random sampling technique. Data were collected with a closed questionnaire of 52 items. The results of the data analysis showed that there was a positive and significant relationship between the quality of student administration services and student satisfaction, as evidenced by the following data analysis: 1) Analysis requirements test: a) a positive relationship test obtained a value of rxy = 0.637> rtable (a = 0.05, n = 74) = 0.226 thus it is known that there is a positive relationship between variable X and variable Y which is in the strong category (0.60 - 0.799). b) The significant relationship test obtained a calculated t value = 7.016 > t table (a = 0.05, df = n-2 = 72) = 1.993, thus there is a significant relationship between variable X and variable Y. Thus Ha, namely a positive and significant relationship between the quality of student administration services and student satisfaction, is accepted and H0 is rejected.